Analisis Pemasaran Komoditas Tomat Di Kelurahan Malumbi Kecamatan Kambera Kabupaten Sumba Timur - Yuventi Mbuamba Naha; Febyningsi R.L. Mbana (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Tomatoes (Lycopersicon esculentum) are one of the horticultural crops widely consumed by the community. Tomatoes are a multipurpose crop that functions not only as a vegetable and fruit, but are also often used as cooking ingredients, sources of vitamins and minerals, natural coloring agents, and even as basic materials for cosmetics and medicines. This plant is easy to cultivate and can be found everywhere, so it has great potential for further development. This study aims to determine the patterns of tomato marketing channels, the marketing margins of tomatoes, and the marketing efficiency of tomatoes in Malumbi Village, Kambera District, East Sumba Regency. Data were collected through interviews using questionnaires and observation. The method used was descriptive, with an approach combining quantitative and qualitative methods. The analyzed data included marketing margins and marketing efficiency.The results showed that the tomato marketing system is carried out through three channels:(1) farmers → consumers, (2) farmers → retailers → consumers,(3) farmers → collectors → retailers → consumers.The total tomato marketing margin obtained in the first channel was 3,000, the total margin in the second channel was 8,000, and the total tomato marketing margin in the third channel was 13,000. The efficiency in channel I was 20.00%, channel II had an efficiency value of 18.7%, and channel III had an efficiency of 43.7%. Thus, the most effective marketing channel is channel II, with a marketing efficiency value of 18.7%.